A Descriptive Analysis of Corporate Governance Mechanisms and Earnings Management in Palestine - Ali Aljadba; Norhaziah Nawai; Nur Hidayah Laili (Journal of Accounting and Investment, 2023)
Research aims: The article aims to describe corporate governance (CG) characteristics and the extent of earnings management (EM) practices in non-financial firms listed on the Palestine Exchange from 2011 to 2018.Design/Methodology/Approach: The study employed the quantitative methodology. Collected data were summarized quantitatively using descriptive analysis with STATA 14. CG data were retrieved manually from published annual financial reports, while financial data for the EM calculation were collected from Thomson ONE.Research findings: Listed non-financial firms in Palestine only moderately complied with the Palestinian Code of Corporate Governance. Some Palestinian firms have also established an audit committee, one of the most important corporate governance mechanisms.Theoretical contribution/Originality: The findings provide insight into CG and EM in Palestine for regulators and policymakers. Practitioner/Policy implication: The results can assist policymakers in strengthening existing regulations and updating the current code of CG or introducing new policies to mitigate EM.